Caesarean section in a patient with Myasthenia Gravis: A bigger challenge for the anesthesiologist than the obstetrician - Manoj K Sanwal; Neha Baduni; Aruna Jain (Wolters Kluwer Medknow Publications, 2012)
Myasthenia Gravis (MG) is an acquired, autoimmune disorder affecting neuromuscular junction presenting with easy fatigability, progressive weakness, diplopia, difficulty in speaking and swallowing and even ventilatory failure in severe cases. During pregnancy the disease may go into remission or may exacerbate at any time during first, second and third trimesters or postpartum period. We are reporting the case of a 28 year old primigravida, known case of MG, who underwent caesarean section and developed muscular weakness on third postoperative day. Her neonate also had tachypnoea and hypotonia, Both, the mother and the baby were managed aggressively and responded well to therapy.